Способи розміщення геральдичного декору в архітектурі - Шукатка, М. С.; Shukatka, M. (Видавництво Львівської політехніки, 2019)
У статті проведено класифікацію геральдичного декору в архітектурі Львова. На основі натурних досліджень фасадів будівель м. Львова виконано композиційний аналіз геральдичного декору, та визначено способи його розміщення в архітектурі.

Architectural decoration is an integral part of the facade of the building and its composition. Heraldic decor complements the architectural image of the building and is an important part of the composition. This type of decor is an integral part of the visual historical-architectural identification in the public space of the city. It indicates the status of institutions, owners and building founders. The heraldic decoration carries an additional semantic load and serves as a marker on the facade of the building. It reflects the history of the city and the state, its role is more important than the usual architectural decoration. Heraldic decoration was explored only in historical works, heraldry, ornamental art and wasn’t considered as a architectural component. In the defensive buildings of the city heraldic decor was used on ancient arsenals, military barracks, gateways and gates of the city wall. These buildings feature a heraldic décor with city and personal icons. As a result of field studies of buildings with heraldic decor, eight ways of placing heraldic decor on the facades were identified. And the method is a crowning decoration, that is, that is located: on the pediments; at the attics, on the porticoes; tongs. The second method – a heraldic decoration placed on the walls of the wings. Buildings with heraldic decoration on the walls can be divided into subgroups: 1 subgroup of this heraldic decoration is located on the framed walls without framing. 2 subgroups of this heraldic decor are located on the walls of a wall in a niche or framing. The third way – the heraldic decoration is located above the entrance of the building. Method IV – the heraldic decoration, decorating the windows. V method – heraldic decor in the metal fencing of balconies. VI method – heraldic decor, decorating columns or pilasters. VII method – heraldic decoration decorating the towers. VII method – heraldic decoration in the sculptural decoration of the facade. The location of the heraldic decoration as an element of the facade is subordinated to the means of the architectural composition: symmetry, asymmetry, rhythm and proportions. The most common is the symmetrical arrangement in which the heraldic is located on the axis or symmetrically relative to the axis. Asymmetric placement is used in buildings with a complex functional scheme, where the symmetrical composition is difficult to implement. In a rhythmic arrangement on the facade, the heraldic decoration is characterized by repetition. The proportions in decorating the facade of the coat of arms also play an important role. Proportional location is subject to the system of golden split and inscribed squares. The described methods of placing prove the importance of heraldic decoration in the facade decoration. Heraldic decoration is involved in the disclosure of the content of the architectural image and is associated with the functional value of the building.
Methods of placing herald decoration in architectur
Keywords: герб; геральдичний декор; фасад будівлі; способи розміщення; композиція фасаду; coat of arms; heraldic decoration; facade of the building; accommodation methods; composition of the facade; 7. 025. 4; 728; 81/82 (477.83)